Association of Craving and Depressive Symptoms in Ketamine‐Dependent Patients Undergoing Withdrawal Treatment - Chen, Lian‐Yu; Chen, Chih‐Ken; Chen, Chun‐Hsin; Chang, Hu‐Ming; Huang, Ming‐Chyi; Xu, Ke (The American journal on addictions, 2020)
Background and Objectives Ketamine has emerged as one of the major illicit substances worldwide. Craving, a primary symptom for addiction, is a key challenge for ketamine abusers attempting abstinence. A link between craving and negative affect has been suggested previously for other substances. We examined the relationship between craving and negative effect (depression and anxiety) in patients with ketamine dependence (KD) undergoing withdrawal treatment. Methods We included 104 patients with KD (76 males and 28 females) who received inpatient treatment for ketamine withdrawal and assessed them by using Beck Depression Inventory (BDI), Beck Anxiety Inventory, and a visual analog scale (VAS; 0‐100 mm) for ketamine craving on day 2 to 3 of admission. Results Fifty‐nine (59%) and 38 (38.7%) of our patients reported moderate‐to‐severe depression and anxiety symptoms, respectively. Patients with greater cravings (ie, greater than the median VAS) reported spending more days on ketamine in the preceding month and displayed severer depressive symptoms than did those with lower cravings. VAS was significantly correlated with BDI scores after adjustment. Patients who stayed in the treatment longer (more than 2 weeks) experienced more cravings and depressive symptoms than those who did not. Discussion and Conclusions We observed a high prevalence of depression in patients with KD, particularly those with higher cravings. Patients with greater cravings and severer depression might require a longer duration of withdrawal treatment. Scientific Significance This research provides intimal evidence for an association between depression and craving in patients with KD. Screening and management of depression are recommended for this population. (Am J Addict 2019;00:00–00)